Assembled mechanical metamaterials with transformable shape and auxeticity. (16th May 2023) - Lang, Jian Ping; Jiang, Wei; Teng, Xing Chi; Zhang, Xue Gang; Han, Dong; Hao, Jian; Xu, Hang Hang; Ni, Xi Hai; Xie, Yi Min; Qin, Qing Hua; Yang, Jian; Ren, Xin
Highlights: Two different assembled honeycomb structures were designed and studied. The structures can be transformed by changing the length of connection plates. The energy absorption capacity of re-entrant honeycomb was investigated. Re-entrant honeycomb has higher energy absorption than hexagonal honeycomb. Abstract: Fabricating auxetic metamaterials via an assembling process is a novel and economic method. In this work, an assembled structure that could realize the conversion of positive and negative Poisson's ratio by changing the length of the connection plates was proposed. Two different honeycomb structures of the assembled re-entrant honeycomb (ARH) and assembled hexagonal honeycomb (AHH) were designed, manufactured and studied numerically and experimentally. Dimensions of the two assembled honeycomb structures are consistent. The nominal stress–strain curves of the two assembled honeycombs have similar initial peak stresses, but the assembled re-entrant honeycomb has a higher bearing capacity and shorter stress plateau. Subsequently, the mechanical properties of ARH were studied by changing the three parameters of corrugated plates. Besides, the energy absorption and specific energy absorption of the assembled re-entrant honeycomb were investigated through the numerical method. Finally, the assembled honeycomb structure with the suitable parameter was determined. Tunable mechanical properties of the assembled auxetic structures can be obtained by varying the length of the connection plates. This strategy of assembly can reduce the costs of manufacturing and improve transportation efficiency. The proposed assembled structures are promising in civil and protective engineering.